(untitled) (American Journal of Smart Technology and Solutions, 2025)
Research has explored the need for an increase in the performance of a Liquid Fuel Swirl Burner (LFSB). An experimental study carried out in LFSB having a varied number of blades and angles of blades yielded the desired improvement. To further improve on the experimental work, extended study is required. This was carried out through Computational Fluid Dynamics Simulation methods, which is cost-effective and have been established to be reliable. This study therefore explores the comparison between experimental results and simulation means to validate the simulation methods and results obtained. The work aimed to enhance thermal combustion in the swirl burner through variations in the blade angles (10°, 20°, 30°, 40°, 45°, 50°, 60°, 70°) and the number of blades in the burner (4, 6, 8, 10 and 12). Computational methods were employed when designing and simulating the burner’s parameters using SolidWorks and ANSYS Fluent. The result showed that the burner with 10 blades at 70° yielded the highest temperature of 1024.547°C and the burner with 12 blades at 10° degrees produced the lowest pressure drop of 11973219.93Pa. Thereby improved combustion was achieved by obtaining the highest temperature at the burner outlet and lowest pressure drop which yielded effective combustion.